التعلّم المعتمد على البطاقات التعليمية لتنمية إتقان المفردات العربية في التعليم غير النظامي - Mochamad Thoriq; Mustain Mustain (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Arabic vocabulary is an essential element in language acquisition; however, its teaching in non-formal education contexts still faces multiple challenges, particularly regarding the limited availability of instructional media and weak learner interaction. Therefore, there is a need to employ simple and effective instructional media, including flash cards. This study aims to describe the use of flash cards in developing vocabulary mastery among fourth-grade students at the Imam Muslim Community Learning Activity Center (PKBM) in Sidoarjo. The study adopted a qualitative approach with a case study design. It involved an Arabic language teacher and several students who were selected purposively. Data were collected through participatory observation, in-depth interviews, and document study, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that the use of flash cards was carried out through stages consisting of card introduction, matching activities, and learning evaluation. This medium also contributed to creating an active, enjoyable, and meaningful learning environment and helped learners strengthen their understanding of vocabulary and retain it in memory. The findings revealed that student motivation and teacher creativity were among the success factors, whereas the main challenges included limited media and differences in learners’ levels. These results indicate that the effectiveness of flash cards is not limited to their visual aspect but is also related to integrated teaching strategies and learner participation. Accordingly, this medium is an appropriate and effective option for teaching Arabic vocabulary in non-formal education settings and opens opportunities for further studies using diverse approaches.